How does domestic violence stigma manifest in women’s lives in Afghanistan? A study of survivors’ lived experiences of help-seeking across three provinces. - Reshmi Mukerji; Lamba Saboor; Sharli Paphitis; Delanjathan Devakumar; Jenevieve Mannell (Global Public Health, 2023)
Afghanistan has one of the highest rates of domestic violence in the world, with an estimated 46% women reporting lifetime violence. Survivors of domestic violence experience significant stigma from their families and communities, often in the form of blame, shame, gossip, and dismissal. While the manifestations of stigma are often the same across cultural settings, the drivers may be different. We conducted sixty semi-structured interviews with survivors of domestic violence in three provinces of Afghanistan. Data were analysed using thematic network analysis. Our analysis highlights stigma as a structural phenomenon in Afghanistan underpinned by mutually reinforcing structural elements (including community, government authorities, marital and natal families, other survivors and the self). In a country with a deeply patriarchal social structure, the main manifestation of stigma was the silencing of survivors of violence, as domestic violence was considered a private affair. Notions of honour were paramount in fuelling stigma against survivors of violence, as any action to report or leave violent relationships was considered dishonourable. Our findings have implications for the design of services to help survivors of violence seek help for the violence they experience, especially at a time when such services are increasingly constricted for women in Afghanistan.